Students’ Perception toward English Online Presentation on Instagram - Mazulfah Mazulfah; Eni Suriyah (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
This study has purpose to know students' perception of English online presentations on Instagram, its advantages and its disadvantages that are seen from students' point of view. A qualitative method was employed in this article. Observation, documentation, and interview are used to collect the data. There are ten students involved in the discussion. The result shows that students positively perceive English online presentations on Instagram. With presentation via Instagram, there are several advantages, including (1) it is neater; (2) no need to open other applications; (3) more concise; (4) easy to use; (5) all presentations and comments are stored securely. However, there are still some drawbacks to using Instagram for presentation, namely (1) not being able to contain all the material and explanations; (2) cannot use audio and video for presentation; (3) requiring a lot of internet quota and a sound signal; (4) students do not focus because they are distracted by other entertainment on Instagram; (5) too many questions; (6) access to Instagram is only owned by lecturers; (7) the audience takes a long time in responding; (8) confusing for some students who have this experience for the first time.